The Zimbabwe government's responses to criticism of Operation Murambatswina - Mhiripiri, Nhamo (Weaver Press, 2021)
Operation Murambatswina was started by the Government of Zimbabwe on 19 May 2005 and quickly grew to include almost all urban centres in the country. Because of its timing and magnitude, it attracted much attention from both domestic and foreign media, and enjoyed various perspectives in terms of reportage. The prominent media visibility and condemnation from some sectors prompted the UN Secretary-General to dispatch a Special Envoy, Anna Tibaijuka, to assess the situation. The UN inspection culminated in a damning report that concluded that the Zimbabwean government and most urban authorities had breached both national and international human rights law provisions guiding evictions, thereby precipitating a humanitarian crisis. Many other local and global critics of the operation registered their own condemnations through different media and forums, accusing the government of human rights abuses, intolerance and insensitivity towards its own citizenry. Internationally, it is now generally accepted that any government's responses to critical human rights condemnations should be taken seriously because they are a strong marker and indicator of the level of concern, tolerance and therefore democracy in that particular country. It also has strong implications for a country's reputation and image. Establishing the range of responses to local and global criticism to Operation Murambatsvina has implications for human rights, democracy and hegemonic rule in Zimbabwe. Such implications can best be deduced from the Zimbabwean government's responses, claims, denials and counterclaims to criticism as reported in the mass media and other sources. Government responses range from public briefings, press releases and official statements to more restricted channels such as direct letters and meetings with delegations, and communications in regional or global agencies. The 'repertoire of government responses' includes any one or a combination of the following: the 'classic' discourse of official denial and rebuttals; converting a defensive position into an attack on the critic; disarmingly acknowledging the criticism; and totally ignoring any public acknowledgement of the criticism and keeping isolated and quiet. Any one of these responses has implications for regime type, regime legitimacy and its claims to practising democracy.